Arabic Learning Curriculum For Non Arab In Rusydi Ahmad Thuaimah’s Version/ منهج تعليم اللغة العربية لغير الناطقين بها عند رشدي أحمد طعيمة - Farid Permana; Syuhadak Syuhadak (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
The Purposes of this research are to reveal Rusydi Ahmad Thuaimah’s opinions about Arabic learning curriculum for non Arabic speaker; and to reveal the model of Arabic learning curriculum for non Arabic speaker betwen Rusydi Ahmad Thuaimah’s version and the previous experts. The type of this research is a library research which using the descriptive and analytative methodes by a qualitative approach. The data research are all about curriculum concept, and the elements of curriculum those taken from Rusydi Ahmad Thuaimah’s books by documentation technique. The data Analysis is used content analysis technique by the steps which are recomended by Krippendorff those are: data making, unitizing, sampling, recording/coding, reducing, inferring n interpreting and results writing. The results of this research are Arabic learning curriculum for non Arabic speaker in Rusydi Ahmad Thuaimah’s version is a system under the big school systems which is planed, determined, done, controled and evaluated by school. This system is integrated with sub-systems those are related by each other like goals, content, methode, evaluation and teacher guidlines. The model of Arabic learning curriculum for non Arabic speaker in Rusydi Ahmad Thuaimah’s version is in line with modern curriculum.